International Students and the Politics of Vulnerability - Deuchar, Andrew (Journal of International Students, 2022)
A significant amount of educational research has foregrounded the challenges international students face while living and learning abroad. While “challenge centric” research has been productive for highlighting the needs of international students, it has tended to reify international students as a vulnerable group in need of intervention. This approach has often downplayed international students’ agency and has not fully moved beyond the boundaries of deficit thinking. This article discusses the implications of framing international students as a vulnerable group before offering some conceptual starting points that might orient future research in more productive directions. It suggests that foregrounding the agency of international students offers a promising mode of reanimating research, and briefly discusses the methodological, conceptual, and political implications of doing so.